Vegetarian diet: Perceptions and attitudes of hospitality management - Šmugović Stefan (University of Novi Sad, Faculty of Sciences, Department of Geography, Tourism and Hotel Management, Novi Sad, 2021)
Vegetarianism is characterized by a great expansion among consumers as well as food producers and suppliers, which significantly affects supply in the hospitality business. Although vegetarians are perceived as a homogenous group, they are a varied and heterogeneous group, depending on the consumed foodstuffs, which requires hospitality workers to offer a wide variety of meals and combinations of plant origin. This is the reason why this research aims to show attitudes of restaurant management towards vegetarian cuisine and to examine the orientation of restaurants towards vegetarian meals, as well as challenges faced by employees in the hospitality industry. The basic task is to examine and present attitudes of hospitality management towards vegetarian food. The aim of the overall research is to get a better insight into awareness and attitudes of hospitality management towards foods of vegetarian origin, which is reflected in the restaurant offer.